Influence of the annealing time on the structural properties for Flash evaporated InSb films - Baghdad Science Journal (مجلة بغداد للعلوم, 2007)
Indium Antimonide (InSb) thin films were grown onto well cleaned glass substrates at substrate temperatures (473 K) by flash evaporation. X-ray diffraction studies confirm the polycrystalline of the films and the films show preferential orientation along the (111) plane .The particle size increases with the increase of annealing time .The transmission spectra of prepared samples were found to be in the range (400-5000 cm-1 ) from FTIR study . This indicates that the crystallinity is improved in the films deposited at higher annealing time.